Effect of four ecotypes of Lepidium peruvianum Chacón on the production of nitric oxide in vitro - Alzamora, Libertad (2006)
The macrophages play an important role in the innate and adaptative response. Upon appropriate activation, macrophages released a variety of cytotoxic mediators like the Nitric Oxide (NO). The objective was to evaluate the production of NO for murine peritoneal macrophages cultivated with methanol extracts (ME) of different ecotypes of Lepidium peruvianum Chacón (at present Lepidium meyenii Walp.) red, black, purple and white. The ME was prepared using maca powdered macerated in methanol (1:2) during 10 days. Peritoneal macrophages were obtained of mice 3 days after having injected them 1 ml of thioglycolate broth; they were cultivated for triplicate during 18 hrs at 37 °C in RPMI 1640 medium supplemented with 10% fetal calf serum. The dose of ME was of 800 μg/ml for ecotype, were considered controls without ME. The production of NO was assayed by nitrite accumulation in the supernatant culture and it was evidenced with Peter Griess’s reagent, the nitrite concentrations were calculated based on the standard curve elaborated with NaNO2 . The produced concentrations of nitrite were of 7,45; 6,79; 5,76; 5,61 and 6,81 mM for the ME purple, black, white, red ecotypes and control respectively, although with the purple ecotype it was superior (p> 0,05).